Effect of Superoxide dismutase on cryopreservation of mithun semen - Ponraj, Perumal; DE, A K; VIKRAM, R; KHATE, K; VUPRU, K; KHAN, M H; NAHAK, A K; MISHRA, P C (The Indian Journal of Animal Sciences, 2022)
The present study was designed to assess the effect of superoxide dismutase (SOD) on post thaw semen quality parameters (SQPs), kinetic profiles and seminal biochemical profiles in mithun. A total of 25 ejaculates were selected and each was split into four equal aliquots after dilution with Tris-citrate-glycerol (TCG) extender such as Group I: control, Group II, III and IV contained 50, 100 and 150 U/ml of SOD, respectively. Cryopreserved and thawed samples were analysed for their motility parameters (progressive forward and in bovine cervical mucus penetration test [BCMPT]), kinetic and velocity parameters by computer assisted sperm analyser (CASA), viability, sperm morphological and nuclear abnormalities, acrosomal, plasma membrane and nuclear integrities and sperm enzymatic leakage and biochemical (sperm cholesterol and antioxidant and oxidative stress) profiles. Study revealed a significant (p <0.05) enhancement in viability, sperm morphological and nuclear normalities, acrosome integrity, motility (progressive and BCMPT), sperm cholesterol content and reduction in leakage of intracellular enzymes in Group III. Moreover, intactness of acrosome and biochemical membranes were protected significantly (p < 0.05) in addition to significant (p < 0.05) improvement in kinetic and velocity profiles in extender containing 100 U/mL SOD. These results clearly suggest that however the cryopreservation of mithun’s spermatozoa in TCG was comparable with other species and inclusion of 100 U/mL SOD holds a clear advantage over control or 50 or 150 U/mL SOD. It can be concluded that SOD supplementation in semen extender can be effectively utilized to reduce the oxidative stress and improved the antioxidant profiles with cascading beneficial effects on cryopreserved semen quality parameters in mithun.